Improving the mass-rearing process of Anastrepha ludens Loew (Diptera: Tephritidae) using a pre-gelatinized starch larval diet - Rivera, J. Pedro; Hernández, Emilio; Toledo, Jorge; Bravo, Bigail; Salvador, Miguel; Gómez, Yeudiel (Instituto de Ecología, A.C., 2012)
The larval diet for mass rearing of the Mexican fruit fly, Anastrepha ludens (Loew) represents 30% of the total cost of production and generates great amount of solid wastes with high contents of protein due to low consumption by larvae. In order to reduce the costs of production and generation pf solid waste, a texturized diet with pre-gelatinized starch was developed, which in comparison to a standard diet, increased the number of larvae per gram of diet from 4.6 to 5, transformation from egg to larva increased from 60 to 76%, larval weight increased from 29.2 to 29.8 mg, and pupal weight from 18.6 to 19.8 mg. It was determined that the percentage of egg hatch at the time of seeding on the diet affected the yield and the transformation from egg to larva. We found that diets seeded when a minimum egg hatch of 40% is reached gave best results. The optimal amount of diet per tray was found to be of 3.0 kg in a layer of 2.0 cm of depth.